Collaboration between Public Health Specialist, Pharmacy Technician, Nursing Technician, Laboratory Medicine, and Health Education Specialist in Enhancing Medication Safety - Laila Abdu Mohamed Dlak; Ayat Mohammed Zain Shami; Amal Gabriel Hamad Athathi; Ghusson Ali Hassan Mathary; Waad Mohammad Hussain Hammami; Asia Eissa Mohsin Alhazmi; Rasha Ali Ibrahim Hakami; Albandry Abdo Fthadin Moafa; Amal Ahmed Ali Sabi; Sharifah Mujalli Mohammed Alnaji; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Positive interactions between two or more health care experts who contribute their special knowledge and skills to help patients make health-related decisions are referred to as interdisciplinary collaboration. It became widely accepted to raise the standard of healthcare in the 1960s and has remained so ever since. It also makes it easier for patients to receive medical services and improves the coordination of care. Medical practitioners gain a great deal from this medical care delivery paradigm as well. These include a lower chance of professional burnout syndrome and increased job satisfaction. Aim: The aim of this review was to explore the integration of public health specialists, nursing and pharmacy technicians,l aboratory technicians and health education in primary health care and its impact on patient outcomes. Methods: Using the search phrases laboratory, nursing, technicians, and pharmacy, patient, public health specialist, health Education, we carried out an extensive search of the electronic literature contained in the MEDLINE database. Restricting the search to articles from 2018 to 2024 allowed us to find pertinent content. To find and read scholarly articles related to our topic, we conducted a Google Scholar search. Certain inclusion criteria influenced the articles’ selection. Results and conclusion : The publications analyzed in this review emphasize that the crucial role of public health specialist, pharmacy technicians, nursing technician, laboratory medicine and health educator in collaboration of health care and their role enhance medication safety and patient outcomes in addition to their contribution has the role to lowchance of professional burnout syndrome and increased job satisfaction of health care team.